Literature as an act of social intervention: the tales of Isaac Rosa (XXI Century. Spanish Literature and Culture, 2016)
Isaac Rosa’s literary works are characterised by the concept of “responsibility” and by the will to okupy a specific literary space that would prevent the triumph of the “other” stories, those contributing to perpetuate the dominant discourse. Therefore, he reclaims that writing short stories is not a banal or minor act, but one of social intervention. In this paper we analyse Rosa’s theoretical proposal and its practical execution. We suggest a thematic classification that will allow to relate his tales with his novels and articles. These three genres address the same topics repeatedly, but the short stories provide an ironical twist on contemporary tragedies that accomplish both an artistic and a politic intention: make the reader to laugh, be shocked, moved and outraged at the same time.
Keywords: Isaac Rosa; responsibility; engagement; social intervention; short story; Spanish contemporary narrative.